Blending by means of partial differential equations - Çinar, A (Int Inst Informatics & Systemics, 2004)
This paper concerns with solving of partial differential equations on blending. In the computer graphics, blending can be defined as joining of objects without sharp edges or corners in the intersection regions of the objects. In this paper, parabolic partial differential equations is used for making blending process. Finite difference method is used for solving these equations. As application, some blend objects are given.
8th World Multi-Conference on Systemics, Cybernetics and Informatics -- JUL 18-21, 2004 -- Orlando, FL
Keywords: blending; parabolic partial differential equations; finite difference method